(untitled) (Journal of Engineering, 2024)
Experimental and numerical investigation has been under taken to study turbulent flow of air through duct using restriction in different shapes and positions for Reynolds numbers ranges of (8.2x104 → 5.6x104).The numerical approach used in this work is the finite volume method for solution of elliptic partial differential equation for the modeling of turbulent (k-) model as well as wall function concept near the wall which was used to take the turbulent effects into consideration have been employed.The experimental test rigs were constructed from Perspex, and a fivehole pressure probe was used to measure the three component of air flow velocity vector in space.The results show that the total pressure drop depends on the shape and position of the restriction, and the pressure drop coefficient due to the restriction shape and position (kR) depends on two parameters; blockage area ratio (Ab) and the ratio between wetted perimeter to the free remainder perimeter (pe/Pe) and dose not depend on the Reynolds number ( for the same blockage area ratio Ab if the pe/Pe increases 40%, the coefficient kR increases 7% , and for the same pe/Pe, if the blockage area ratio increases 50% ,the coefficient kR increases 10%). But the pressure drop coefficient due to the friction (Cf) is a function of Reynolds.